Records of Trial from Thomas Shepard’s Church in Cambridge, 1638–1649 - Rogers-Stokes, Lori. author. aut Link
XII, 190 p. 16 illus.
Keywords: This book presents a revolutionary new reading of manuscript records left by puritan minister Thomas Shepard in Cambridge, Massachusetts that have been studied for decades as his on-the-spot recording of oral relations of faith delivered by candidates for church membership. This book proves that these records are not relations, but Shepard’s personal record of sessions of trial—meetings with candidates still working out their spiritual seeking. New transcriptions of the original manuscript records, and corresponding never-before-published writing by Shepard, dispel much of the confusion produced by the published transcriptions. Close-readings of the manuscripts, contrasted with the published transcriptions, set the stage for a new understanding of puritan spiritual preparation in Shepard’s Cambridge church. The book concludes with a challenge to the negative reading of the women’s records that is central to established scholarship, revealing their powerful, confident spiritual identities and voices.